Komunikasi Politik dalam Demokrasi Pemilihan Kepala Daerah - Syahrul Sitorus (Sekolah Tinggi Agama Islam Sumatera Medan, 2015)
Political communication is a tool and a means that facilitates the delivery of the message. The message here can be in the form of symbols talks as words, pictures, or tindakan. can also by a combination of emblems to generate stories, photo (still picture or motion picture), also staging a drama. In this case, interest groups and political parties serve as channels that allow contacts between officials of the political and administrative officials as well as with the people. Contacts often make their relationship became more familiar with each other. It can thus be built up of political communication in both vertical and horizontal.